PERAN INTRANET DALAM MENJEMBATANI KOMUNIKASI INTERNAL DI CORPORATE - Imran, Maharani; Maharani Imran (Fakultas Komunikasi, Sastra, dan Bahasa, 2011)
This study is to explain that an internal and corporate communication between staff and management can be achieved effectively and efficiently through cooperation and harmonious working climate. The method is a descriptive analytic using a study of literature with qualitative analysis. The result shows that corporate need an intranet as an internal media to facilitate communication and information access. Intranet is a public relations media to promote sharing of knowledge, data storage, and dissemination of information, rules, and ideas and provide security, access to personal information that can be relied upon the company. Intranet is an effective internal communication in corporate.